2020
DOI: 10.15244/pjoes/114262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Decontamination Performance of Three Permeable Bricks: Adsorption and Filtration Experiments

Abstract: To investigate the removal mechanism of pollutants from urban rainfall runoff by permeable brick, ceramic brick, cement brick and steel slag brick were applied to study their decontamination performance. An adsorption experiment with granular materials obtained by crushing the bricks and a filtration experiment with complete bricks were carried out, and suspended solids (SS), chemical oxygen demand (COD), total organic carbon (TOC), dissolved organic carbon (DOC), ammonia nitrogen (NH 4 +-N), total nitrogen (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results showed that these combinations were effective in removing pollutants from pavement runoff, with a removal rate of more than 82% for SS, 49% to 75% for COD, 60% to 67% for petroleum, and 30% to 47% for heavy metals. The removal rate for SS, petroleum, COD, Cu, and Zn in combination were found to be superior to those of permeable bricks (20-32%) [18]. The average concentrations at 0.3EAC were reduced from 92.6 mg/L to 8.2 mg/L for SS, 12.08 mg/L to 4.72 mg/L for petroleum, 45.1 mg/L to 22.64 mg/L for COD, 1.5 mg/L to 1 mg/L for Cu, and 0.49 mg/L to 0.34 mg/L for Zn.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that these combinations were effective in removing pollutants from pavement runoff, with a removal rate of more than 82% for SS, 49% to 75% for COD, 60% to 67% for petroleum, and 30% to 47% for heavy metals. The removal rate for SS, petroleum, COD, Cu, and Zn in combination were found to be superior to those of permeable bricks (20-32%) [18]. The average concentrations at 0.3EAC were reduced from 92.6 mg/L to 8.2 mg/L for SS, 12.08 mg/L to 4.72 mg/L for petroleum, 45.1 mg/L to 22.64 mg/L for COD, 1.5 mg/L to 1 mg/L for Cu, and 0.49 mg/L to 0.34 mg/L for Zn.…”
Section: Resultsmentioning
confidence: 89%
“…Shukla et al [17] used the chemical oxygen demand (COD) as an index to describe the organic compounds and showed that the activated carbon in a chemical lab can absorb SS and COD at a relatively high rate, ranging from 43% to 100%. Lin et al [18] indicated that physical retention in the surface layer of the bricks plays a crucial role in the SS filtration process. However, it is difficult for one method to achieve the ideal treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research efforts on quantitative performance evaluation need to be extended for structural stability, permeability, pollutant removal capability, and socioeconomic viability of PPs. Material properties and the pore size of the surface layer significantly affect the infiltration capability and water quality of runoff [27,28]. Li et al [19] reported that shale brick more efficiently removes the pollutants from surface runoff as compared to other materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, permeable brick pavements have become one of the most frequently used low impact development (LID) techniques [ 1 , 2 , 3 ]. This infiltration-based technology is comprised of structural layers with relatively high porosity to allow rainwater to pass through its surface brick and underlying structure.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 8 ] revealed that the average removal efficiency of TSS was approximately 90.0% for six commonly used permeable pavement materials because of physical interception. Zizeng et al [ 2 ] also found that the physical interception of the surface layer played a critical role in the SS filtration process, and the uniform and dense pore distribution was instrumental in the retention of particulates. Due to the high removal capacity of TSS in urban runoff, sediment is captured in the voids within the pavement material, and physical blockage occurs [ 9 ], which is why clogging has been defined as the accumulation of silt within the brick due to sedimentation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%